Mikrostruktur, Porositas Dan Sifat Mekanik Beton Curing Air Laut - Bachtiar, Erniati; Setiawan, Asri Mulya; Setiawan, Arman; Fudlailah, Pratiwi (Jurnal Talenta Sipil, 2024)
When constructing buildings in coastal areas, contact between the materials used and sea air is sometimes unavoidable. Before the concrete reaches its maximum strength at the age of 28 days, it can be exposed to contamination from sea air. Consequently, chemical reactions involving cement, air, and sea air become inevitable. The research aims to ascertain the microstructure, porosity, and mechanical properties (compressive strength and tensile strength) of high-performance concrete utilizing the Self Compacting Concrete method. Two variations of concrete samples are considered, involving differences in the curing water used and the age of the concrete. There are two curing variations: concrete cured with fresh water and concrete cured with seawater. The concrete's age is monitored at 1, 3, 7, 28, and 90 days. In the microstructure analysis of seawater-cured concrete, chloride compounds, ettringite, and Friedel's salt were identified. Both compressive strength and splitting tensile strength show an increase with the concrete curing age, and they are inversely proportional to the concrete's porosity. The mechanical properties of freshwater-cured concrete are slightly lower than those of seawater-cured concrete. However, the difference is negligible, meaning they are nearly identical at both 28 days and 90 days.